Development of Rhythmic Gymnastics Model for Early Childhood Movement Activities - Pranoto, Nuridin Widya; Rahman, Gali; Fauziah, Varhatun (Faculty of Sport and Health Sciences, 2025)
Motor development in early childhood (ages 4–6 years) is fundamental to children’s physical, cognitive, and socio-emotional growth. However, structured and developmentally appropriate movement programs in Early Childhood Education remain limited. This study aimed to develop and evaluate a rhythmic gymnastics model tailored to young learners using the ADDIE model. A research and development approach was employed, including needs analysis, model design based on music and fundamental movements, prototype development, expert validation, and field testing. Nine experts assessed the model using a 4-point Likert scale covering content, movement design, musical suitability, and practicality. Field trials involved 33 children across three early childhood institutions, supported by observations and teacher feedback. The results showed high validity, with Aiken’s V values of 0.8074 (complexity), 0.7778 (suitability), and 0.6568 (motivation). Implementation findings indicated active child engagement and positive teacher responses regarding ease of use and contextual relevance. Overall, the model is valid, practical, and effective in supporting holistic motor development, offering a feasible approach to enriching movement-based learning in early childhood education.